Protection of the marine environment in developing counties: management of nutrient inputs / Nicholas Kathijotes - Kathijotes, Nicholas (Faculty of Architechture , Planning & Surveying, 2011)
The management and treatment of sludge in developing countries, from on-site sanitation systems has neither been addressed by problem holders nor by researchers. All septic tanks need to be desludged regularly in order to maintain a certain level of treatment efficiency and minimize ecological and eventual marine pollution incidences. Practices followed in developing countries are discussed and lessons learned are emphasized for promoting sustainable community development. Stakeholder identification and participation and their cooperation through the process, as well as new regulations on service provision and management procedures are addressed in this study.